A severe case of sympathetic ophthalmia – case report - Matysik-Woźniak, Anna; Kątski, Wojciech; Lewandowska-Furmanik, Maria; Żarnowski, Tomasz; Pawłowska-Wakowicz, Barbara (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Purpose: The aim of our work is to present clinical and histological data of the case of severe sympathetic ophthalmia (SO). Sympathetic ophthalmia is a rare, bilateral, non-necrotizing granulomatous panuveitis that follows penetrating injury to one eye. SO is a potentially blinding condition. Material and methods: A 40 years old man sustained a penetrating injury to his right eye. He refused to be treated surgically. A few days later, he developed bacterial endophthalmitis. After 5 months the patient came to our hospital with clinical manifestations suggesting SO. His right eye was removed. Unfortunately, despite the intensive pharmacological treatment the uveitis of the left eye intensified. Results: Generalized uveitis with optic nerve oedema, secondary cataract and glaucoma resulted in total blindness. Conclusions: Although, SO is a rare disease, ophthalmologists should be aware of its devastating effect on vision.